EMBA academic visit to University of Canberra Australia / Hazliza Haron - Haron, Hazliza (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2020)
A group of MBA students of part 2 and part 3 went on an academic trip to University of Canberra, Canberra, and University of New South Wales, Sydney.